Myofibroblasts and Transforming Growth Factor-Beta1 in Reactive Gingival Overgrowths - Apostolos Epivatianos; Dimitrios Andreadis; Savas Iordanidis (eJournal of Oral Maxillofacial Research)
Objectives: The aim of this study was to detect the presence of myofibroblasts and transforming growth factor-beta1 in fibrous and ossifying-fibrous epulis and their possible contribution to the collagenous connective tissue formation. The correlation between the myofibroblasts and the degree of inflammatory infiltration was also examined. Material and Methods: The presence of myofibroblasts as well as transforming growth factor-beta1 was examined in twenty cases of fibrous epulis and 22 ossifying fibrous epulis, using immunohistochemistry. Results: Myofibroblasts positive for alpha smooth muscle actin and vimentin but negative to desmin were found in 20% and 45% in fibrous epulis and ossifying fibrous epulis, respectively. Myofibroblasts were distributed in areas with and without inflammatory infiltration and their presence in inflammatory areas was not related with the degree of inflammatory infiltration. A percentage of 21 - 60% of fibroblasts and chronic inflammatory cells expressed transforming growth factor-beta1 in all cases. Conclusions: These data suggest that transforming growth factor-beta1 and myofibroblasts contribute to the formation of collagenous connective tissue in fibrous epulis and ossifying fibrous epulis. Myofibroblasts are mainly presented in ossifying fibrous epulis than in fibrous epulis. It seems to be no relationship between the presence of myofibroblasts and the degree of inflammatory infiltration of the lesions.